FT-IR spectroscopic studies of major organic matter in carbonaceous chondrites using microscopic technique and comparison with terrestrial kerogen - Murae, Tatsushi (National Institute of Polar Research, 1994)
P(論文) Infrared (IR) absorption spectra of major types of carbonaceous matter in four Antarctic carbonaceous chondrites (Y-74662,Y-791198,ALH-77307,Y-791717) and two non-Antarctic carbonaceous chondrites (Murchison, Allende) were taken using a microscopic FT-IR technique. Without any treatment for concentration of carbon, powdered samples of carbon-rich C2 chondrites such as Y-74662,Y-791198,and Murchison gave spectra of the carbonaceous matter with enough intensity by focusing the beam on carbonaceous aggregates. Carbon-poor C3 chondrites (ALH-77307,Y-791717,and Allende) necessitated carbon enrichment by acid treatment to give IR spectra of carbonaceous matter of adequate intensity. The IR spectra indicated the presence of similar functional groups in the major types of carbonaceous matter of all of the investigated chondrites. Some natural coals (typical terrestrial kerogen) show very similar IR spectra to the carbonaceous matter of carbonaceous chondrites. departmental bulletin paper